Income related inequalities in self assessed health in Britain: 1979–1995. Issue 2 (1st February 2003) - Gravelle, H; Sutton, M
Abstract : Study objective: To measure and decompose income related inequalities in self assessed health in England, Scotland, and Wales, 1979–1995. Design: The relation between individual health and a non-linear transformation of equivalised income, allowing for sex, age, country, and year effects, was estimated by multiple regression. The share of health attributable to transformed income and the Gini coefficient for transformed income were calculated. Inequality in health was measured by the partial concentration index, which is the product of the Gini coefficient and the share of health attributable to transformed income. Participants and setting: Representative annual samples of the adult population living in private households in Great Britain 1979–1995. The total analysed sample was 299 968 people. Main results: Pro-rich health inequality was largest in Wales and smallest in England over the period because the effect of increased income on health was greatest in Wales and least in England. In all three countries, pro-rich health inequality increased throughout the period. In the early 1980s this was primarily attributable to increases in income inequality. Thereafter the increased share of health attributable to income was the principal cause. Conclusions: Reductions in pro-rich health inequality can be achieved by reducing income inequality, reducing the effect of income on health, or both.